An Exploration of High School Students’ Attitudes Towards Online English Language Learning - Ly Sovann; Nhean Voithna; Soeurn Chenda (UNIB Press, 2025)
The attitude of students in language learning is progressively considered key success of language learning. However, high school students at the research setting find it challenging to study online. Therefore, students’ attitude towards online learning is very crucial to explore. To fulfill this study, the researcher created two main research objectives including the exploration of high school students’ attitudes toward learning the English language online, and the challenges of high school students while learning online. A quantitative method design was established to gather data. 236 high school students were requested to complete questionnaires This study discovered that most students had 17 items positive attitude towards learning English in online classes and 4 items with low agreement showing that online classes are not fun, and not easy to achieve high scores, and not relevant to gender causing EFL learners’ anxiety. In addition, students had a positive attitude towards 9 items of the usefulness of online learning to improve their skills and knowledge. They also showed a positive attitude toward online classes in the improvement of their four 21st-century competencies. Moreover, they agreed that online classes are accessible and convenient. However, they also faced some challenges in their learning such as spending much money on internet service, no internet connection, complicated online tools, no smart devices, and difficult to form activities. Based on the result, internet connection, online teaching and learning, and orientation should be provided and trained to students before implementing the programs.